Ethical Capital; Religious Education and Graduate Employability - Choirunni’mati Akmal, Rasya; Daryono (Journal Economic Business Innovation, 2025)
Purpose: The aim of the present study is to explore the role of ethical capital in graduate employability, as measured by the economic worth attributed to character, as it is understood within the context of religious education, through the framework of university training.Method: The present study employs a quantitative cross-sectional design, with a sample of 312 undergraduate students from public and private universities in Semarang, Indonesia. Hierarchical multiple regression analyses were performed in SPSS 28.Findings: The internalization of religious values, the quality of religious pedagogy, and the institutional religious climate have been identified as significant positive predictors of professional character formation. Furthermore, the students' self-perception of being prepared for a career structure is influenced by these associations even more powerfully, suggesting that if students understand that the market values virtue, they are far more likely to turn their religious education into professional character.Novelty: The present study proposes a novel conceptualization of "ethical capital" that integrates moral philosophy, educational theory and the economics of business. This is the first study to provide empirical evidence for the hypothesis that self-awareness of career readiness functions as a key moderator in clarifying the efficacy of religious education in developing religiously oriented, character-retention career skills. This finding addresses contradictions across the national and regional literature.Implications: University leaders must reframe religious education as a core component of employability strategy. This requires developing curricula for deep value internalization, training lecturers in transformative pedagogy, and aligning institutional policies to create a virtuous ecosystem that maximizes both ethical development and economic return.